Security of Cryptocurrencies in blockchain technology: State-of-art, challenges and future prospects. (1st August 2020) - Ghosh, Arunima; Gupta, Shashank; Dua, Amit; Kumar, Neeraj
Abstract: In contemporary era of technologies, blockchain has acquired tremendous attention from various domains. It has wide spectrum of applications ranging from finance to social services and has greatly influenced the emerging business world. Since, blockchain technology is getting embedded in the e-commerce services, the cryptocurrencies are gaining huge prevalence. Bitcoin and ethereum are few such crypto currencies, which have utilized decentralized nature of blockchain. Blockchain can be considered as a distributed database system containing immutable ledgers, which are prone to attack by malicious users. Although, from the initial digital currency to the present smart contract, the utilities of blockchain have been harnessed, the innovative technology has to rely on cryptography for its security. There are several reports, which emphases on the vulnerabilities and security of blockchain, however, there is a lack of a comprehensive and methodical survey in both application and technical views. In this survey article, the authors cover various aspects related to blockchain including its taxonomies and the situations in which a particular category of blockchain should be applied. The authors also focusses on the structure of blockchain and the working of the ongoing transactions in the cryptocurrency network. In addition, the authors also specify various categories of consensus protocols, smart contracts, forks, techniques for generating the consensus. A detailed taxonomy of blockchain along with their features and related real-world applications is also discussed. In addition, existing key platforms of blockchain related to the cryptocurrencies, hyperledger and multichain are also discussed. Existing emerging vulnerabilities of blockchain related to the recent attacks on bitcoin and etherum is also presented along with the defensive methodologies and future trends in blockchain.